Name Similarity Encourages Generosity: A Field Experiment in Email Personalization - Munz, Kurt P.; Jung, Minah H.; Alter, Adam L. (Marketing Science, 2020)
Email field experiment varying whether potential donor has matching surname to in-need teacher and quantifying effectiveness of less-exact matches.